Contemporary diagnosis of lower urinary tract dysfunction. - Rosier, Peter (F1000Res, 2019)
Introduction: Diagnosis of lower urinary tract (LUT) dysfunction starts with categorization in clinical syndromes, and initial management is based on the assumptions about pathophysiology that these syndromes contain. However, clinical practice guidelines are ambiguous in clinical specialists’ diagnosis of dysfunction after failure of initial management. This is a narrative and critical review of the existing evidence, and the aim is to suggest practice improvements in the process of clinical specialists’ diagnosis for patients resistant to initial management. Methods and Results: Evidence is collated on the basis of the author’s personal preference in combination with good clinical practice general principles. Statements and suggestions to improve reflect personal opinion. For two groups of patients with LUT dysfunction, the strategy of initial diagnosis is summarized and desirable principles of secondary care diagnosis are discussed. More specifically, a structure for the contemporary care of women with signs and symptoms of urinary incontinence is described and for that of the group of men older than 45 years with symptoms of LUT dysfunction. Conclusions: Urodynamic testing is the undisputed gold standard for objective assessment and is the only way to stage and grade the dysfunction. Clinical practice guidelines and clinical specialists are too modest about the use and applicability of objective or urodynamic testing for referred persons with LUT dysfunction that is resistant to initial pragmatic management. Objective assessment and diagnosis are mainstays in secondary care, and the indication to perform objective assessments in patients with LUT dysfunction should be advised much more specifically in guidelines and practice recommendations.